Implementasi Hamilton Anxiety Rating Scale untuk Mendiagnosis Tingkat Kecemasan pada Mmahasiswa Dalam Penyusunan Skripsi - Elfrida Veranda Beka Dede; Sebastianus Adi Santoso Mola; Yelly Yosiana Nabuasa (J-ICON : Jurnal Komputer dan Informatika, 2022)
Students who do thesis generally feel anxious. Lack of motivation and creativity, and there are still many students who find it difficult to write scientific papers are the main causes of anxiety. This anxiety needs to be addressed immediately so as not to have an impact on the writing time of the thesis which will be longer. Students can consult with a psychiatrist or psychologist to deal with anxiety. However, the inefficient consulting service becomes a problem due to the unbalanced comparison between the population in East Nusa Tenggara and clinical psychologists. Therefore, we need a system that has the experience and knowledge of an expert to determine the level of anxiety of students who are writing a thesis using the Hamilton Anxiety Rating Scale (HARS) and forward chaining inference. From the results of the research conducted, it is known that forward chaining inference is proven to be able to be applied and accurate in diagnosing anxiety levels in students who are writing thesis with 100% accuracy.